Association between Resistin and High Sensitive Troponin I in St Elevation Myocardial Infarction and Systolic Heart Failure - Wasyanto, Trisulo; Febrilia, Laurent (Indonesian Journal of Medicine, 2020)
Background: Nearly half of all patients with acute myocardial infarction (AMI) have left ventricular systolic dysfunction and one-third have symptoms of heart failure (HF). In patients with AMI the resistin level correlated inversely with left ventricular ejection fraction (LVEF). Increased levels of high sensitive (hs) troponin I are associated with poorer prognosis. This study aimed to determine the association between levels of resistin and hs troponin I in ST elevation myocardial infarction (STEMI) patients with systolic HF.Subjects and Method: This was a cross-sectional study was conducted at Dr. Moewardi General Hospital, Surakarta, from April 1 to May 31, 2018. A sample of 32 patients who admitted which diagnosed with STEMI was selected for this study. They were divided into two group according to result of LVEF measurement, LVEF < 40% and LVEF ≥ 40%. Blood examination and transthoracic echo-cardiography were performed to all patients. Correlation test using partial and multiple correlation test. To different 2 mean using Mann Whitney test.Results: Mean of patient age was 59.5 years old. Resistin decreased LVEF (r= -0.41; p= 0.009), and it was statistically significant. Hs troponin I decreased LVEF (r= -0.25; p= 0.081), but it was marginally significant. Resis-tin level and hs troponin I increased LVEF (r= 0.47; p= 0.025), and it statistically significant.Conclusion: There was an association between resistin and hs troponin I level together in STEMI patients with systolic HF. There was an association of resistin levels in STEM I patients with systolic HF. There was no association of hs troponin I levels in STEMI patients with systolic HF.Keywords: Resistin, hs troponin I, STEMI, systolic heart failure.Correspondence: Trisulo Wasyanto. Department of Cardiology and Vascular Medicine, Faculty of Medicine, Universitas Sebelas Maret/ Dr. Moewardi Hos-pital. Jl. Kol. Sutarto 132, Surakarta 57126, Central Java, Indonesia. Email: trisulo.wasyanto@gmail.com.Indonesian Journal of Medicine (2020), 5(1): 1-9https://doi.org/10.26911/theijmed.2020.05.01.01